Minimally invasive hysterectomy for benign disease: our experience study - Kiran, Talakere Usha; Katke, Rajshree Dayanand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The incidence of hysterectomy in India ranges from 7-8 % and 60% of major gynaecological surgeries are hysterectomies at government teaching institutions. The objective of this study was to assess feasibility and safety of laparoscopic hysterectomy. Methods: It was a retrospective case series. Study duration was two years. Setting was at Cama and Albless hospital which is a government hospital affiliated to grant medical college, Mumbai. Cases with benign indication for hysterectomy were which were unsuitable for vaginal approach were assessed and those deemed suitable for laparoscopic approach were selected. Total laparoscopic approach was used to perform hysterectomy. Patient demographics and outcome measures were analyzed. Outcome measures included duration of surgery, length of postoperative stay, estimated blood loss, complication rate and laparotomy conversion rates. Results: It was a two year study period. Total number of women who underwent hysterectomies during this period for benign indications were 303, out of which 146 were done by vaginal route, 126 by abdominal route and the remaining 35 (22%) were done by laparoscopic route. Main indication was dysfunctional uterine bleeding not responding to medical management. Median age of patients was 43 years, majorities were parous and none of them were obese. Uterine size ranged from normal size to 16 weeks. Duration of surgery was between 1.5-2.5 hours with an estimated blood loss of less than 100 ml in 2/3rd of them. Median duration of postoperative stay was 7 days. The major complication and laparotomy conversion and readmission rates were nil. Conclusions: Laparoscopic hysterectomy was well accepted and was found to feasible and safe in our setting.